Optimization of the Hydrogen‐Adsorption Free Energy of Ru‐Based Catalysts towards High‐Efficiency Hydrogen Evolution Reaction at all pH. Issue 36 (24th May 2019) - Cheng, Min; Geng, Hongbo; Yang, Yang; Zhang, Yufei; Li, Cheng Chao
Abstract: The utilization of noble‐metal catalysts for the hydrogen evolution reaction (HER) provides an efficient strategy for hydrogen acquisition. However, exploring catalysts with suitable hydrogen binding strength for the HER process is always of great importance, but extremely challenging. In this work, sulfur and phosphor as electron‐withdrawing elements were incorporated into carbon nanotube (CNT)‐supported Ru catalysts, which were prepared through a facile solution reduction reaction and post thermo treatment. Owing to the suitable electronegativity provided by P and synergistic effects of the carbon nanotubes, the RuP2 /CNT achieved a high catalytic performance as a HER electrocatalyst. This may result from the modulation effect of the electronic properties and the depressed adsorption free energy of RuP2 . Electrochemical tests present that the RuP2 /CNT composite exhibit a small overpotential of 58 mV at 10 mA cm −2 in acidic electrolyte. In a neutral or alkaline environment, the overpotential is 82 and 40 mV, respectively. The RuP2 /CNT electrode also possesses stable durability for long‐time cycling, suggesting its remarkable property as promising all‐pH HER catalyst. Abstract : Who is the best? Owing to the suitable electronegativity provided by P and synergistic effects of the carbon nanotubes, the RuP2 /CNT composite achieved high catalytic performance as a hydrogen evolution reaction (HER) electrocatalyst. This may result from the modulation effect of the electronic properties and the depressed adsorption free energy of RuP2 (see scheme).